ANALISIS KEBUTUHAN DALAM PENGEMBANGAN MEDIA AUDIO BAHASA INGGRIS UNTUK PEMBELAJARAN MENYIMAK PADA SISWA SMP N 5 NGAWEN GUNUNGKIDUL - nFn Suparti (Kwangsan: Jurnal Teknologi Pendidikan, 2018)
This study aimed at presenting need analysis results related to listening skill problems encountered by the students of SMP N 5 Ngawen, Gunungkidul and the format of English audio media for teaching listening skills which was conducted between March till April 2018. There were 50 students, two practisioners, and two native speakers involved in this study.  The data were collected by using two kinds of instruments namely questionnaires and an interview guide. The results showed that: (1) the language ability of the students were relatively low although 92% of the students had learned English since they were in the kindergarten or elementary schools; (2) 58% students considered that listening was the most difficult skills among the three other skills (reading, writing, speaking); (3) the listening problems faced by the students were categorized into three aspects, namely: the content aspects, the environment aspects, and the learner aspects. The first aspect included vocabularies, sentences/expressions, pronunciation, the length of the texts, and the speed in reading the scripts. The second aspect is about the environment/atmosphere aspect included namely the quality of the audio programmes; facilities, and noise. The third was the learner aspects namely the sub-skills of listening comprehension. Moreover, there were some information related to the technical aspects namely the ideal duration of an audio program and the format of the English audio media. In fact, the results of the research could be used as a guidance in designing a model of English audio media for improving listening skills among the target students. AbstrakPenelitian ini bertujuan untuk mendapatkan informasi mengenai permasalahan pembelajaran menyimak (listening) dan kebutuhan pembelajaran listening pada siswa SMPN 5 Ngawen, Gunungkidul. Penelitian dilakukan pada bulan Maret-April 2018 dengan metode pengumpulan data berupa kuesioner dan wawancara. Sampel diambil dengan teknik simple random sampling yang melibatkan 50 responden siswa. Selain siswa, penelitian ini melibatkan tiga praktisi pendidikan/guru dan dua native speakers. Hasil analisis kebutuhan menunjukkan bahwa: (1) kemampuan Bahasa Inggris siswa rendah meskipun 92% responden siswa telah belajar Bahasa Inggris sejak TK/SD;  (2) 58% siswa menganggap listening merupakan keterampilan bahasa tersulit dibanding reading, writing, dan speaking; dan (3) permasalahan dalam pembelajaran listening meliputi aspek materi, lingkungan/atmosfir, dan dari sisi pebelajar/learners. Aspek materi yang diungkap meliputi pemilihan tema, kosakata, kalimat/ujaran, pronunciation, panjang pendek input text, dan kecepatan berbicara. Aspek lingkungan/atmosfir meliputi kualitas audio, peralatan, dan noise/kegaduhan saat pemutaran media sedangkan dari sisi pebelajar meliputi sub-skills dalam listening comprehension yang belum dikuasai dan perlu dikuasai siswa. Selain itu, diperoleh juga informasi terkait hal teknis misalnya durasi audio dan format sajian media. Secara umum, hasil analisis kebutuhan ini dapat dimanfaatkan sebagai pedoman dalam menyusun rancangan model media audio pembelajaran listening untuk siswa SMP pada tahapan kedua dalam proses pengembangan desain instruksional, yaitu tahapan desain.